Skewness analysis on Japanese stocks, random portfolios, industry portfolios and market indices. - Ng, Yi Ting. (2008)
We study skewness of stocks in Japan with particular emphasis on industry portfolios. Industry portfolios are unique as they are formed from stocks that tend to move in the same fashion and possess similar cyclical tendencies. We find that the formation of industry portfolios helps to ‘preserve’ positive skewness and this skewness persists over time.